章太炎 『齊物論釋』에서 인과론 부정의 세 가지 층위 - 김영진; Kim Youngjin (중국학보, 2025)
章太炎은 중국 근대의 저명한 사상가이자 학자이다. 그는 청대 고증학에 정통했으며, 불교와 서양철학을 학습하여 비교적 독창적인 사상을 형성하였다. 그의 가장 중요한 철학 저작은 『齊物論釋』으로, 제목에서 알 수 있듯이 이 저작은 『장자』의 「제물론」에 대한 주석 형식을 빌려 자신의 철학을 전개한 작품이다. 특히 그는 이 글에서 대승불교의 중요한 유파인 유식학의 이론을 적극적으로 활용하여, 「제물론」에 등장하는 다양한 개념을 해석하였다. 그는 「제물론」이 유식학의 교의와 대체로 잘 부합하지만, 인과론 문제에서는 서로 충돌한다고 보았다. 장타이옌은 「제물론」이 불교의 연생법을 부정하고, 無因論의 입장을 지지한다고 해석한다. 그러나 그의 인과론 부정은 단순하거나 일관되지 않고, 복잡하고 혼란스러운 측면이 있다. 필자는 장타이옌의 인과론 부정을 논리와 사상 자원의 측면에서 세 가지 층위로 구분하여 이해할 수 있다고 본다. 첫째, 장타이옌은 연생법이 무한소급의 오류나 상호인과의 오류에 빠질 수 있다고 지적하는데, 비록 그가 명시적으로 언급하지는 않았지만, 이는 『중론』의 논리를 따르고 있는 것으로 보인다. 둘째, 그는 無自性의 인과론을 바탕으로 존재의 성립과 지속을 설명하며, 이때 유식학의 상 속설 이론을 차용한다. 셋째, 존재의 성립과 지속을 보다 구체적으로 설명하고, 인과론 부정이 허무주의로 귀결되는 것을 방지하기 위해 『대승기신론』의 唯心不覺과 眞如心體 등 형이상학적 개념을 도입한다. 본고는 이러한 세 층위를 중심으로 장타이옌의 인과론 비판의 논리 구조와 사상적 의미를 분석함으로써, 인과에 대한 그의 철학적 사유를 고찰한다. Zhang Taiyan was a prominent thinker and scholar in modern China. He was well-versed in Qing dynasty evidential scholarship and developed an original philosophical system by integrating Buddhist and Western philosophical thought. His most significant philosophical work is Interpretation of the Qiwu Lun, which, as the title suggests, is a commentary on the “Qiwu Lun” chapter of the Zhuangzi. In this work, Zhang actively applies the theories of Yogācāra Buddhism to interpret various concepts from the Qiwu Lun. While he sees broad compatibility between the Qiwu Lun and Yogācāra doctrine, he argues that they conflict on the issue of causality. Zhang interprets the Qiwu Lun as rejecting the Buddhist doctrine of dependent origination (pratītyasamutpāda) and instead upholding a theory of non-causality. However, his critique of causality is not simple or consistent; rather, it is complex and at times contradictory. This study identifies three distinct levels in Zhang Taiyan’s critique of causality, based on his logical method and philosophical sources. First, although he does not explicitly mention it, Zhang draws on the logical structure of Nāgārjuna’s Mūlamadhyamakakārikā to point out the fallacies of infinite regress and mutual causation in the theory of dependent origination. Second, in explaining the formation and continuation of existence through a causality devoid of self-nature (svabhāva), he adopts the Yogācāra concept of “continuity theory” (xiangxushuo). Third, to provide a more concrete account of the generation and persistence of phenomena―and to avoid the nihilistic implications of denying causality―he introduces metaphysical concepts from the Awakening of Faith in the Mahāyāna, such as “unenlightened consciousness” (weixin bujue) and the “true mind-substance” (zhenru xinti). By analyzing these three levels, this paper explores the logical structure and philosophical implications of Zhang Taiyan’s critique of causality, thereby shedding light on the nature of his causal thought.